Design and Development of Small Chamber-Type Low-pressure Plasma Surface Treatment Equipment to Improve the Shear Bond Strength of Materials for Dental Prostheses - Moon, Byung-Kwon; Ko, Kyoung-Tag; Lee, Jong-Tak; Ji, Min-Kyung; Bang, Jun-Ho; Ryu, In-Ho (International Journal of Engineering and Technology, 2018)
Background/Objectives: This study was to design a small chamber-type equipment by investigating the influence of dental prostheses treatment on the shear bond strength.Methods/Statistical analysis: The equipment was designed for the requirement of dental prostheses surface treatment. Two groups of zirconia disks were treated with low-pressure plasma (LP) by the prepared equipment (13.7 mA, 625V, 8.6W and minimum vacuum degree) and atmospheric plasma jet (AP), individually. In addition, untreated disks were regarded as the control. One-way ANOVA analysis was used to compare different surface treating groups.Findings: The output of power supply graph indicated the equipment was obtained the steady power(48kHz). On comparison, it existed a statistically significant different between the LP group and the control group (p<0.05). However, the results of the LP group and AP group were similar. Among the all, the highest shear bone strength value was found in the LP group (8.50Â±2.87MPa) and the lowest in the control group (5.57Â±3.28MPa). The low-pressure plasma surface treatment seems to have a better ability than other types of surface treatment (atmospheric plasma jet, etc.). Moreover, it is expected to be utilized in treating the surface of dental prostheses with plasma.Improvements/Applications: This LP surface treatment equipment for dental prostheses was found to function better than other surface treatment equipments. It is optimal to develop in the dental prostheses modified field.Â